A Variational Binary Level Set Method for Structural Topology Optimization (Communications in Computational Physics, 2013)
This paper proposes a variational binary level set method for shape andtopology optimization of structural. First, a topology optimization problem is presented based on the level set method and an algorithm based on binary level setmethod is proposed to solve such problem. Considering the difficulties of coordinationbetween the various parameters and efficient implementation of the proposed method,we present a fast algorithm by reducing several parameters to only one parameter,which would substantially reduce the complexity of computation and make it easilyand quickly to get the optimal solution. The algorithm we constructed does not needto re-initialize and can produce many new holes automatically. Furthermore, the fastalgorithm allows us to avoid the update of Lagrange multiplier and easily deal withconstraints, such as piecewise constant, volume and length of the interfaces. Finally,we show several optimum design examples to confirm the validity and efficiency ofour method.